(untitled) (Rudarsko-geološko-naftni zbornik, 2021)
The conditions of coal seam mining in the mines of Ukraine have been considered. The problem of conducting coal mining by longwalls in the conditions of soft adjoining rocks, which concerns the protection of mine roadways located near the face, has been revealed. In such conditions, the existing protective constructions are ineffective due to the fact that they yield and get pressed into the soft rocks of the footwall. This indicated the need for research into the geomechanical state of soft rocks of the footwall. According to the results of known studies on the mechanism of rock mass failure around roadways and the data of physical and mechanical properties of the coal mass, which is represented by soft rocks, the correlation dependence has been obtained, the use of which allowed for the determination of the parameters of the rock deformation diagram and the establishment of the stability criterion of footwall rocks under the protection means and stability conditions of the geotechnical system “protective construction – adjoining rocks.” They are the basis of a new approach to ensure the stability of the roadways, which are supported behind the faces, by controlling the stress state in the system “protective construction – adjoining rocks.” This may be the basis for the development of new methods of protecting roadways in conditions of soft adjoining rocks.